2013
DOI: 10.1063/1.4817899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of etching with cysteamine assisted phosphoric acid on gallium nitride surface oxide formation

Abstract: In-situ functionalization of polar GaN was performed by adding cysteamine to a phosphoric acid etchant in order to study its effect on photoluminescence and oxide formation on the surfaces. The functionalization was characterized by atomic force microscopy, x-ray photoelectron spectroscopy, photoluminescence (PL), and water contact angle measurements. Two sets of polar GaN samples with different dislocation densities were evaluated, thin GaN layers residing on sapphire and thick free-standing GaN separated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…49,50 For thiol functionalization, the water contact angle response varied more by the different etchant temperatures used rather than the presence or lack thereof of cysteamine. 41 The decrease in water contact angle is more sensitive to the surface topography (the quantity and size of surface defects), which was seen at higher temperatures. Although cysteamine presence on the surface was identified, the surface coverage was not uniform.…”
Section: A Topographical Changesmentioning
confidence: 96%
See 4 more Smart Citations
“…49,50 For thiol functionalization, the water contact angle response varied more by the different etchant temperatures used rather than the presence or lack thereof of cysteamine. 41 The decrease in water contact angle is more sensitive to the surface topography (the quantity and size of surface defects), which was seen at higher temperatures. Although cysteamine presence on the surface was identified, the surface coverage was not uniform.…”
Section: A Topographical Changesmentioning
confidence: 96%
“…From the atomic ratios, it was found that the addition of cysteamine to polar bulk and thin layer samples resulted in an increase in the nitrogen content on the surface. 41 The bulk nonpolar samples showed an increase in environmental carbon contamination when any of the etching processes were performed. 50 The nonpolar samples provided insight into the oxide sensitivity of the bulk and thin layer samples, as mentioned previously.…”
Section: B Surface Chemistry Changesmentioning
confidence: 99%
See 3 more Smart Citations